Using multivariate diagnostics to assess the functional status of children with cerebral palsy. - Vindiuk Pavel Andreevich (Kharkov National Pedagogical University, 2011)
The considered assessment of energy supply from children with cerebral palsy. The study involved 16 children with spastic forms of cerebral palsy secondary school age. The use of testimony bagatofaktonoї rapid diagnosis in this population. It is established that the rate of functional status of children with cerebral palsy grow under the influence of physical rehabilitation.